2024
DOI: 10.1002/pssa.202300878
|View full text |Cite
|
Sign up to set email alerts
|

Anodic Niobium–Titanium Oxide Crossbar Memristor Arrays for pH Sensing in Liquids

Dominik Knapic,
Elena Atanasova,
Ivana Zrinski
et al.

Abstract: Anodic Nb–Ti oxide crossbar memristor arrays are successfully produced on Si substrates. Their use as pH sensors is tested by analyzing their current–voltage (I–U) sweeps in Ringer´s solutions with different pH values. A gradual evolution of the memristive hysteretic curve is observed upon pH variation. A sensor calibration showing a linear trend with least square error close to 1 is performed and the performance of the pH sensing is assessed. The limit of detection (LOD), limit of quantification (LOQ), and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 66 publications
2
0
0
Order By: Relevance
“…Thus, compositional fluctuations lead to oxide stoichiometry variation, which may influence the O species kinetics. This qualitative finding is in line with quantitative XPS analysis of anodized Nb-Ti alloys that previously revealed the oxide compositions change with the depth [47]. In particular, for the Nb-46 at% Ti anodic oxide, it was found that the Ti amount increases from 46% in the parent metal to 52% in the mixed oxide.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Thus, compositional fluctuations lead to oxide stoichiometry variation, which may influence the O species kinetics. This qualitative finding is in line with quantitative XPS analysis of anodized Nb-Ti alloys that previously revealed the oxide compositions change with the depth [47]. In particular, for the Nb-46 at% Ti anodic oxide, it was found that the Ti amount increases from 46% in the parent metal to 52% in the mixed oxide.…”
Section: Resultssupporting
confidence: 89%
“…In particular, for the Nb-46 at% Ti anodic oxide, it was found that the Ti amount increases from 46% in the parent metal to 52% in the mixed oxide. This indicates a gradient in the Ti (and complementarily Nb) content within the oxide, which is discussed from the point of view This qualitative finding is in line with quantitative XPS analysis of anodized Nb-Ti alloys that previously revealed the oxide compositions change with the depth [47]. In particular, for the Nb-46 at.% Ti anodic oxide, it was found that the Ti amount increases from 46% in the parent metal to 52% in the mixed oxide.…”
Section: Resultssupporting
confidence: 85%